Kekristenan di tengah Pluralitas: Analisis 1 Petrus 2:11-17 - Vayen Limpele (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Abstract: Indonesia is a country consisting of various differences (Race, Culture, Ideology, religious). These differences have shaped this country. Pancasila is the basis of Indonesia so this country continues to exist even though there are various differences/diversities. Diversity is certainly beautiful but it is not impossible that in diversity there are conflicts on the basis of differences, then the understanding of pluralism emerges to make the nation aware that even though we are different in ideology, belief, and culture, we are still both human and one nation. So that between us creates a feeling of mutual respect and respect for each other, not bringing each other down. The author uses a descriptive qualitative research method with a literature study approach to see how Christianity is in the midst of plurality. In Christianity, Exclusivism in Christian theology can make Christians mistaken in responding to a plurality of diversity if exclusivism is not properly understood. The author sees that 1 Peter 2:11-17 is the answer to how Christians should behave in the midst of this Plurality, because in this letter it teaches that Christians must abstain from fleshly desires, and emphasizes that as servants of God one must have a good way of life. and righteous before God, in the midst of a nation that does not share one belief regardless of religious differences.Abstrak: Indonesia merupakan negara yang terdiri dari berbagai perbedaan (Ras, Budaya, Ideologi, religius). Perbedaan itulah yang telah membentuk negara ini. Pancasila sebagai dasar Indonesia membawa negara ini terus eksis manakalah terdapat berbagai perbedaan/keberagaman. Keberagaman tentu indah namun bukan tidak mungkin di dalam keberagaman terjadi konflik atas dasar perbedaan, maka muncul paham pluralisme untuk menyadarkan bangsa bahwa meski berbeda secara ideologi, kepercayaan, dan budaya namun kita tetap sama-sama manusia dan sama-sama satu bangsa, agar di antara kita tercipta perasaan saling menghargai dan saling menghormati bukan saling menjatuhkan. Penulis menggunakan metode penelitian kualitatif deskripsi dengan pendekatan studi literatur untuk melihat bagaimana Kekristenan di tengah Pluralitas. Di dalam kekristenan, Eksklusivisme teologi Kristen bisa saja membuat orang Kristen keliru dalam menyikapi pluralitas keberagaman jika eksklusivisme itu kurang tepat dipahami. Penulis melihat bahwa 1 Petrus 2:11-17 adalah jawaban mengenai bagaimana sikap orang Kristen di tengah Pluralitas ini, sebab dalam surat ini memberikan pengajaran bahwa orang Kristen harus menjauhkan diri dari keinginan daging, dan menegaskan bahwa sebagai hamba Allah haruslah memiliki cara hidup yang baik dan benar di hadapan Allah, di tengah bangsa yang tidak satu kepercayaan terlepas dari perbedaan agama.